Optimal component-scale design of ejector refrigeration systems based on equivalent temperature. (1st April 2020) - Akbari, H.; Sorin, M.
Highlights: A two-step approach for the design of ejector refrigeration system is introduced. The entropy generation inside the ejector is calculated, independently of working fluids. The most appropriate working fluid is selected based on the economic analysis. Abstract: The article proposes a comprehensive approach for the design and optimization of an ejector refrigeration system, including the selection of the optimal working fluid. The ejector refrigeration system is modeled as the combination of a power sub-cycle and a vapor compression sub-cycle, and the ejector is modeled as an expander-compressor device. The approach applies the equivalent temperature concept in two steps. The first step is a system-scale optimization of the ejector refrigeration system that is independent of the working fluid. Minimization of the total system thermal conductance was chosen as the objective function where a second-law analysis constrains the optimization problem. The first step includes the pre-selection of refrigerant candidates based on some thermodynamic, environmental and safety criteria. The second step is the component-scale design of the ejector refrigeration system, comprising the calculation of all remaining unknown temperatures, pressures, and mass flow rates. The second step includes the selection of the working fluid. If the coefficient of performance and total thermal conductance, as economic indicators, are not sufficient to choose the optimal working fluid, then an exergoeconomic analysis is used to make the final selection. The proposed comprehensive approach was demonstrated with a case study and validated against published results.